2015
DOI: 10.1074/mcp.m114.041947
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Malonylation Is Elevated in Type 2 Diabetic Mouse Models and Enriched in Metabolic Associated Proteins

Abstract: Protein lysine malonylation, a newly identified protein post-translational modification (PTM), has been proved to be evolutionarily conserved and is present in both eukaryotic and prokaryotic cells. However, its potential roles associated with human diseases remain largely unknown. In the present study, we observed an elevated lysine malonylation in a screening of seven lysine acylations in liver tissues of db/db mice, which is a typical model of type 2 diabetes. We also detected an elevated lysine malonylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 39 publications
3
99
0
Order By: Relevance
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), which converts glyceraldehyde 3-phosphate to glycerate 1,3-bisphosphate, was the second most dynamically regulated glycolytic enzyme (WT/KO ratio = 6.4) (Figure 4C). Interestingly, Du et al (2015) recently reported hypermalonylation of Aldolase B in db/db mouse liver, though its regulation by SIRT5 was not addressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), which converts glyceraldehyde 3-phosphate to glycerate 1,3-bisphosphate, was the second most dynamically regulated glycolytic enzyme (WT/KO ratio = 6.4) (Figure 4C). Interestingly, Du et al (2015) recently reported hypermalonylation of Aldolase B in db/db mouse liver, though its regulation by SIRT5 was not addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Intra-cellular concentrations of malonyl-CoA are highly dynamic; during fasting or in livers of diabetic rats, levels are reduced by approximately 50% (McGarry et al, 1978; Guynn et al, 1972). Du et al (2015) recently reported the hypermalonylation of liver proteins in a mouse model of diabetes and the potential for this malonylation to inhibit glycolytic enzyme function. Here, we directly demonstrate both a potential role for malonyl-CoA as a negative feedback regulator of glycolysis and a role for SIRT5 in limiting this negative feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 20 types of natural amino acids occurred in proteins, lysine is one of the most heavily modified residues12. Recent discoveries of multiple types of new protein lysine acylations, such as malonylation, succinylation, and glutarylation, have greatly expanded our understanding of the types of protein PTMs13456789. Because malonyl, succinyl and glutaryl groups contain a negatively charged carboxyl group, the three types of acidic lysine modifications are structurally similar and have the potential to regulate different proteins in different pathways5.…”
mentioning
confidence: 99%
“…A recent study characterized that lysine malonylation regulates the glycolytic flux by modifying mouse glyceraldehyde 3-phosphate dehydrogenase (GAPDH) at K184 to inhibit its enzymatic activity3. Also, using the liver tissues of db / db and ob / ob mice, it was observed that malonylation plays a potential role in type 2 diabetes, whereas further bioinformatic analysis of the proteomic results revealed the enrichment of malonylated proteins in metabolic pathways, especially the pathways of glucose and fatty acid metabolisms4.…”
mentioning
confidence: 99%